Economic Growth and Unemployment Nexus: Okun’s Two-Version Case for Nigeria, South Africa and United States of America - Onakoya, Adegbemi Babatunde; Victor, SEYINGBO, Adedotun (Journal of Economics and Behavioral Studies, 2020)
Okun’s law in its original form was predicated on the experience in the United States of America. Some methodological refinements have been added based on studies conducted in other climes with varied results. This research investigated the applicability of this law in Nigeria, South Africa and the United States of America. The study conducted a comparative analysis of three of the versions of the law. The research employed Ordinary Least Squares method having validated it’s appropriateness with Dickey-Fuller and Philips-Perron tests. The demonstrated superiority of the dynamic version over the difference version was manifest in all the countries. The result also showed that the dynamic version of the law was applicable in the three nations while the difference version showed the lack of linkage between economic growth and unemployment only in Nigeria. Deployment of employment creative employment schemes, labour market reform and economic restructuring are recommended in the Nigerian case. The policy makers on South Africa and USA are enjoined to pursue growth- inducing policies.